Pengaruh Produksi Perikanan Tangkap dan Budidaya Laut terhadap Kontribusi PDRB Perikanan di Kabupaten Kepulauan Meranti: Penelitian - Dini Dwi Putri; Putri Tabita; Sinta Ramadani; Vanda Iswara Putri; Rasyid; Taryono (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the influence of capture fisheries and marine aquaculture production on the contribution to the Gross Regional Domestic Product (GRDP) of the fisheries sector in Kepulauan Meranti Regency during the 2019–2024 period. This research is motivated by the importance of the fisheries sector as one of the main pillars of the coastal regional economy, especially in island regions where communities are heavily dependent on fisheries activities. Despite having great potential, the contribution of the capture fisheries and marine aquaculture subsectors to the regional GRDP shows diverse dynamics due to environmental changes, technology, and socio-economic factors of coastal communities. The research method employed is a quantitative method with descriptive and associative approaches. The data used are secondary data obtained from the Central Statistics Agency (BPS) of Riau Province and the Department of Marine Affairs and Fisheries (DKP) of Kepulauan Meranti Regency. Research variables include capture fisheries production, marine aquaculture production, and fisheries GRDP contribution. Data analysis was conducted using a multiple linear regression model to examine the simultaneous and partial effects of both fisheries subsectors on the economic added value of the fisheries sector in the region. The research findings indicate that capture fisheries production has a significant influence on increasing the fisheries sector GRDP, demonstrating that fish capture activities remain the backbone of the coastal community's economy. Meanwhile, marine aquaculture production provides a relatively fluctuating contribution but shows an increasing trend from year to year, indicating the great potential of this subsector to be developed as a new sustainable source of economic growth. Overall, the improved performance of both fisheries subsectors plays an important role in strengthening the regional economy, creating new employment opportunities, and improving the welfare of communities in Kepulauan Meranti Regency.